2022
DOI: 10.3390/ijerph19137628
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Competence in Primary School Children: Examining the Effect of a Psycho-Educational Group Intervention: A Pilot Prospective Study

Abstract: Emotional competence (EC) is a key component of children’s psychological, cognitive, and social development, and it is a central element of learning. The primary goal of this study was to evaluate the effectiveness of implementing a psycho-educational group intervention aimed at improving children’s emotional competence (EC), quality of integration and scholastic skills. A total of 229 children (123 females; M Age = 7.22 years; SD = 0.97 years) completed the Pictures of Facial Affect (POFA), the Drawn Stories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…In the last decades, many studies have shown the fundamental role of emotions on psycho-educational processes during childhood and how good emotion management can be a pathway to better social competence in future ( La Grutta et al, 2022 ). Particularly, current evidence shows that children may be able to express emotions through drawings even if they are unable to communicate or express them verbally ( Fury et al, 1997 ; Malchiodi, 1998 ; Kim and Suh, 2013 ; Pace et al, 2013 ; Goldner et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decades, many studies have shown the fundamental role of emotions on psycho-educational processes during childhood and how good emotion management can be a pathway to better social competence in future ( La Grutta et al, 2022 ). Particularly, current evidence shows that children may be able to express emotions through drawings even if they are unable to communicate or express them verbally ( Fury et al, 1997 ; Malchiodi, 1998 ; Kim and Suh, 2013 ; Pace et al, 2013 ; Goldner et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, social–emotional competence could be considered a critical factor to target with universal preventive interventions that are conducted in schools because the construct associates with social, behavioral, and academic outcomes that are important for healthy development; predicts important life outcomes in adulthood; can be improved with feasible and cost-effective interventions; and plays a critical role in the behavior change process ( Domitrovich et al, 2017 ; La Grutta et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that at the post-intervention assessment, students showed a decreased score on violence and alexithymia scales. Similarly, in 2022 La Grutta et al [ 9 ] conducted a psychoeducational program among 229 students aimed to increase children’s emotional competence and scholastic skills. They found that students reported positive changes in emotional recognition after the intervention with better levels of emotional health and psychological well-being and a possible future positive impact on cooperative skills and greater school success.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence supports the effectiveness of youth programs in reducing alexithymia, improving the ability to recognize and express emotions [ 6 , 7 , 8 , 9 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%